ANALISIS EFISIENSI USAHATANI PADI SAWAH DI KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - MADE SUMA WEDASTRA (SOSIAL SAINS DAN TEKNOLOGI, 2022)
This research is a descriptive research conducted in Narmada District, West Lombok Regency by taking a sample of 60 farmers, proportionally random sampling on the basis of the widest rice field area in the 2020/2021 rainy season. Data collection methods are observation, documentation and interviews using questionnaire data collection tools. Data were analyzed by cost and profit analysis and RC ratio analysis   From the results of the study it can be concluded that: 1). The average profit of lowland rice farming in Narmada District, West Lombok Regency is Rp.19,240,124.81 /ha/season, 2). Lowland rice farming in Narmada District is efficient and feasible to be developed with the acquisition of R/C = 2.87. This means that for every one rupiah that is sacrificed for financing lowland rice farming, will receive an income of Rp 2.87.